Technology-Based Learning Management at State Vocational Schools In Minahasa Selatan - Vidlina Lie; Deitje A Kauutuk; Ronny Palilingan; Henny N Tambingon (Green Publisher Indonesia, 2022)
The purpose of this study was to analyze and describe technology-based learning management at SMKs in South Minahasa Regency. Technology-based learning management is a form of learning management that utilizes technological learning instruments to support the teaching and learning process to obtain optimal learning outcomes. The results of the study indicate that the management of technology-based learning has begun to be carried out by the three SMKs which are the current research locations, namely through planning, implementation and evaluation. These three schools already have sufficient supporting facilities for the implementation of technology-based learning management, however, there are still weaknesses and deficiencies that need to be addressed, especially by the Education Office and especially school principals so that the use of technology can be more optimized to support optimal learning outcomes.